Respuestas

2013-04-04T01:15:40+02:00

Sean a,b y c las medidas de los lados del triangulo. entonces

 

     a=2b-2             y         a=c+3    2b-2=c+3       entonces  c=2b-5                                                                      

 

     reemplazando      2b-2+b+2b-5=23   entonces desarrollando 5b=30

                                                                                                        b=6

                                                                               entonces           a=10    y    c=7